2018
DOI: 10.1029/2018gl079203
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of ENSO Events Unified by Convective Threshold Sea Surface Temperature: A Nonlinear ENSO Index

Abstract: We show that the well‐known failure of any single index to capture the diversity and extremes of El Niño‐Southern Oscillation (ENSO) results from the inability of existing indices to uniquely characterize the average longitude of deep convection in the Walker Circulation. We present a simple sea surface temperature (SST)‐based index of this longitude that compactly characterizes the different spatial patterns, or flavors of observed and projected ENSO events. It recovers the familiar global responses of temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(110 citation statements)
references
References 55 publications
4
106
0
Order By: Relevance
“…By contrast, in the instrumental data, the Niño 3 region shows the strongest relationship with SWNA among the various tropical Pacific indices. The longitudinally dependent relationship between the tropical Pacific and SWNA supports the idea that the eastward extent of convection plays an important role in determining extratropical impacts of El Niño-Southern Oscillation events, and predetermined regional "boxes" (e.g., the Nino3 or Nino3.4 indices) may be insufficient to adequately represent the continuum of variability in the tropical Pacific (Williams & Patricola, 2018).…”
Section: Teleconnection Patterns During Wet and Dry Years In Swna In supporting
confidence: 64%
See 2 more Smart Citations
“…By contrast, in the instrumental data, the Niño 3 region shows the strongest relationship with SWNA among the various tropical Pacific indices. The longitudinally dependent relationship between the tropical Pacific and SWNA supports the idea that the eastward extent of convection plays an important role in determining extratropical impacts of El Niño-Southern Oscillation events, and predetermined regional "boxes" (e.g., the Nino3 or Nino3.4 indices) may be insufficient to adequately represent the continuum of variability in the tropical Pacific (Williams & Patricola, 2018).…”
Section: Teleconnection Patterns During Wet and Dry Years In Swna In supporting
confidence: 64%
“…While the Niño3.4 index can broadly illustrate the state of the tropical Pacific during SWNA droughts, the previous analysis does not fully encompass potential impacts from other parts of the tropical Pacific or other ocean regions (e.g., McCabe et al, ; Seager et al, ; Ashok et al, ; Weng et al, ; Coats, Smerdon, et al, ; Coats et al, ; Williams & Patricola, ). Specifically, recent work has suggested that multiple remote factors, other than the tropical Pacific, may lead to persistent high pressure over the North Pacific and unusually dry conditions in SWNA (e.g., Teng & Branstator, ; Swain et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…), and the resultant patterns can be dependent on the technique employed. A tailor-made climate index was developed for this study, largely due to a desire to preserve nonlinearity in the climate system and retain more information than off-the-shelf univariate indices provide (Williams & Patricola, 2018). The technique employed is a WT-based framework which has been used to explore climate variability in many of the physical processes relevant to coastal erosion and flooding extremes (e.g., .…”
Section: A1 Weather-type Classifications and Chronologymentioning
confidence: 99%
“…Johnson and Xie et al (2010) used this property to explain that the "threshold" for deep atmospheric convection will increase at the same rate as the tropical mean SST in response to anthropogenic climate change. RSST has to date mostly been used in the global warming context, for instance, to understand the spatial patterns of changes in tropical cyclones (as aforementioned), in the hydrological cycle (e.g., Xie et al, 2010), and to define ENSO events (Williams & Patricola, 2018) and their convective signature (Johnson & Kosaka, 2016) in a warming world. RSST also allows isolating the ENSO and IOD signals in the context of global cooling induced by tropical explosive volcanic eruptions (Izumo et al, 2018;Khodri et al, 2017).…”
Section: 1029/2019gl086182mentioning
confidence: 99%